The effect of the industrial zone on the chemical composition of some medicinal plants - Abdykhalikova, K.A.; Yergalieva, E.M.; Chashkov, V.N. (KSU Publ., 2017)
Biological characteristics of medicinal plants is largely determined by the place of their growth. This article presents the results of a study the influence of the industrial zone on the vegetation, the study of the influence of anthropogenic factors on the chemical composition of medicinal plants — hawthorn, sea buckthorn, yarrow growing in different conditions. The impact of industrial natural geotechnical systems is considered by the influence of JSC SSGPO (Sokolov-Sarbai Mining Production Association) and the adjacent territory of Rudny city. Sokolov-Sarbai Mining Production Association develops deposits of iron ore by open pit and underground methods. Analysis was performed with fruit, which is harvested from the territory of the industrial mining zone, and with fruit which is harvested on the rural territory, located at a more remote distance from the industrial zone, and pharmacy samples (Shymkent city). Alkalimetric method used for determining the total acidity of all samples. Qualitative analysis of organic acids was carried out by a method of paper chromatography, where the acids are extracted with a mixture of ether and acetone. The quantitative content of vitamin C (ascorbic acid) was determined by iodometric method. The quantitative content of tannins was determined by a permanganat-metric method. To confirm the presence of the iron, aluminum, calcium ions in samples harvested in the industrial area was determined by the ash content.
Дəрілік өсімдіктердің химиялық құрамына өндіріс орындарының əсері
Влияние промышленной зоны на химический состав лекарственных растений
Keywords: medicinal plants; phytochemicals; hawthorn (Crataégus); sea Buckthorn (Hippóphaë rhamnoídes); yarrow (Achilléa millefólium); qualitative analysis; quantitative analysis; environment